2015
DOI: 10.1038/ncomms7776
|View full text |Cite
|
Sign up to set email alerts
|

Targeting matriptase in breast cancer abrogates tumour progression via impairment of stromal-epithelial growth factor signalling

Abstract: Matriptase is an epithelia-specific membrane-anchored serine protease that has received considerable attention in recent years due to its consistent dysregulation in human epithelial tumors, including breast cancer. Mice with reduced levels of matriptase display a significant delay in oncogene-induced mammary tumor formation and blunted tumor growth. The abated tumor growth is associated with a decrease in cancer cell proliferation. Here we demonstrate by genetic deletion and silencing that the proliferation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 54 publications
0
58
1
1
Order By: Relevance
“…In the polyoma middle T antigen-induced breast cancer model, genetic or pharmacological inhibition of TF, matriptase, and PAR2 all blunt tumor growth. 29,[76][77][78] Matriptase plays a critical role in pro-HGF activation and c-Met signaling in this model. 77 The role for coagulation proteases in matriptase activation, the importance of matriptase for PAR2 activation, and relative roles of PAR2 and HGF downstream of matriptase remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the polyoma middle T antigen-induced breast cancer model, genetic or pharmacological inhibition of TF, matriptase, and PAR2 all blunt tumor growth. 29,[76][77][78] Matriptase plays a critical role in pro-HGF activation and c-Met signaling in this model. 77 The role for coagulation proteases in matriptase activation, the importance of matriptase for PAR2 activation, and relative roles of PAR2 and HGF downstream of matriptase remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…29,[76][77][78] Matriptase plays a critical role in pro-HGF activation and c-Met signaling in this model. 77 The role for coagulation proteases in matriptase activation, the importance of matriptase for PAR2 activation, and relative roles of PAR2 and HGF downstream of matriptase remain to be determined. Matriptase activation by coagulation proteases argues that pro-HGF, pro-urokinase, and other matriptase substrates should be considered alongside PARs and fibrin downstream of TF in tumor growth and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The role of matriptase in vivo has also been studied in detail in breast cancer. In an oncogene-induced mouse mammary carcinoma model, hypomorphic matriptase mice with reduced levels of matriptase displayed a significant delay in tumor formation and blunted tumor growth (Zoratti et al, 2015). The reduced tumor growth was associated with a profound decrease in cancer cell proliferation.…”
Section: Matriptasementioning
confidence: 99%
“…Mechanistic studies demonstrated that the proliferation deficiency was caused by the impairment of carcinoma cells, in cell lines and in vivo, to initiate the activation of the c-Met signaling pathway in response to fibroblast-secreted pro-hepatocyte growth factor (pro-HGF) (Figure 1). In primary mammary carcinoma cells and human breast cancer cell lines, addition of HAI-1 and HAI-2 inhibited pro-HGF mediated c-Met signaling and cell proliferation (Zoratti et al, 2015). Importantly, inhibition of matriptase catalytic activity using a selective small-molecule inhibitor efficiently abrogates the activation of c-Met, Gab1 and AKT, in response to pro-HGF, which functionally leads to attenuated cancer cell proliferation and invasion.…”
Section: Matriptasementioning
confidence: 99%
“…First successful proof of concepts studies with prostate cancer models in mice have been performed with the arginal-derived matriptase inhibitor CVS-3983 pancreatic adenocarcinoma cell line AsPC-1 21 . Even stronger effects on pro-HGF/SF induced c-Met activation on primary mammary carcinoma cells and three other human breast cancer cell lines were described for the ketobenzothiazole inhibitor IN-1 22 ( Figure 1), meanwhile various highly potent ketonederived inhibitors have been described 23,24 . The invasiveness and migration of various tumor cell lines could be also inhibited by other benzamidine-derived matriptase inhibitors 25,26 .…”
Section: Introductionmentioning
confidence: 99%